The influence of culture in IT governance implementation: a higher education multi case study - Bianchi. I.; Dinis de Sousa, R.; Pereira, R.; De Haes, S. (International Journal of Human Capital and Information Technology Professionals, 2019)
IT governance calls for the definition and implementation of formal mechanisms at the highest level in the organization taking into account structures, processes and relational mechanisms for the creation of business value from IT investments. Several factors can influence IT Governance implementation success. Culture is one of these factors and the one this research will focus on. Seen as probably the most difficult factors to change since it is grounded on practices performed over time, it should receive special attention. This article aims to analyze how culture can influence IT Governance implementation of structure, process and relational mechanisms in the context of higher education. Ten case studies in universities from three different countries: Brazil, Portugal and Netherlands were carried out. The purpose is the identification of relevant differences in IT Governance implementation among organizations from the following cultures: uncertainty avoidance and individualism. This article concludes by presenting key contributions, limitations and future work.